Beneficial effect of zinc chloride and zinc ionophore pyrithione on attenuated cardioprotective potential of preconditioning phenomenon in STZ-induced diabetic rat heart. (May 2016) - Jamwal, Sumit; Kumar, Kushal; Reddy, B V Krishna
Ischemic preconditioning (IPC) is well demonstrated to produce cardioprotection by phosphorylation and subsequent inactivation of glycogen synthase kinase-3β (GSk-3β) in the normal rat heart, but its effect is attenuated in the diabetic rat heart. This study was designed to investigate the effect of zinc chloride and zinc ionophore pyrithione (ZIP) on the attenuated cardioprotective potential of IPC in the diabetic rat heart. Diabetes mellitus (DM) was induced by a single intraperitoneal administration of streptozotocin (STZ) (50 mg/kg; i.p). The isolated perfused rat heart was subjected to 30 minutes of ischemia followed by 120 minutes of reperfusion. Myocardial infarct size was estimated by triphenyltetrazolium chloride (TTC) staining and cardiac injury was measured by estimating lactate dehydrogenase (LDH) and creatine kinase-MB (CK-MB) in the coronary effluent. Also, GSK-3β was measured and neutrophil accumulation was measured by estimating myeloperoxidase (MPO) levels. IPC significantly decreased the myocardial infarct size, the release of LDH and CK-MB, the GSK-3β levels and the MPO levels in the normal rat heart. Pre- and post-ischemic treatment with zinc chloride and zinc ionophore pyrithione (ZIP) in the normal and diabetic rat hearts significantly decreased the myocardial infarct size, the level of CK-MB and LDH in the coronary effluent and GSK-3β and MPO levels. Our results suggest that pharmacological preconditioning with zinc chloride and ZIP significantly restored the attenuated cardioprotective potential of IPC in the diabetic rat heart.